Nb2SiTe4 and Nb2GeTe4: Unexplored 2D Ternary Layered Tellurides with High Stability, Narrow Band Gap and High Electron Mobility - Fang, Wen-Yu; Li, Ping-An; Yuan, Jun-Hui; Xue, Kan-Hao; Wang, Jia-Fu (Journal of electronic materials, 2020)
Recently, two-dimensional (2D) ternary layered telluride materials have attracted enormous attention due to their exotic electronic properties. Here, we propose two new monolayer 2D semiconductors Nb 2 SiTe 4 and Nb 2 GeTe 4 , which show high dynamic, thermodynamic and mechanical stability. Nb 2 SiTe4 and Nb 2 GeTe4 have stable three-dimensional layered bulk counterparts, and monolayer Nb 2 SiTe4 and Nb 2 GeTe4 have low cleavage energies such that exfoliation of bulk material becomes a viable means for the preparation of mono- and few-layer materials. Indirect band gap of 0.80 eV and 0.63 eV have been revealed in monolayer Nb 2 SiTe4 and Nb 2 GeTe4. Acoustic phono-limited carrier mobilities are estimated, where monolayer Nb 2 SiTe 4 exhibits high electron mobilities up to 1775 cm 2 V −1 s −1 and 1222 cm 2 V −1 s −1 along a and b directions, respectively. Analysis of mechanical properties reveals that 2D Nb 2 SiTe 4 and Nb 2 GeTe 4 are positive Poisson’s ratio materials with moderate Young’s moduli. The bonding characteristics have been investigated through electron localization function and Bader charges. Pronounced light absorption is predicted in the visible light and ultraviolet regions. These findings render 2D Nb 2 SiTe 4 and Nb 2 GeTe 4 attractive candidates for future nanoelectronics and optoelectronics.